I Don’t Have Power, and I Want More: Psychological, Physical, and Sexual Dating Violence Perpetration Among College Students - Toplu-Demirtaş, Ezgi (Journal of interpersonal violence, 2022)
The purpose of this study was to (a) explore the prevalence of, and gender differences in, self-reported physical, sexual, and psychological violence perpetration in dating relationships (i.e., not married or engaged), (b) evaluate the factorial validity of the Power Perceptions and Power Satisfaction Questionnaire in dating relationships, and (c) document the mediating role of power satisfaction in the associations between power perception and physical, sexual, and psychological dating violence perpetration. College students (N = 812) completed the Power Perceptions and Power Satisfaction Questionnaire and the Psychological Aggression, Physical Assault, and Sexual Coercion subscales of the Revised Conflict Tactics Scale. Gender differences emerged in the prevalence of physical (43.0% for women and 35.0% for men) and sexual violence (25.0% for women and 41.8% for men) but not psychological violence (80.1% for women and 75.5% for men). Exploratory factor and parallel analyses yielded two subscales of power perceptions and power satisfaction, which explained 40.56% of the variance. Mediation analyses revealed that college students who perceived lower relationship power were more dissatisfied with that relationship power and, in turn, perpetrated more physical, sexual, and psychological violence against their partners. The mediation effects were evident in both women and men. The implications of the current findings for future research and mental health professionals at colleges are outlined.